The Influence of Financial Ratios on Financial Distress in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesian Stock Exchange - Siswanto Siswanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The objective of this study is to ascertain the financial ratios, specifically the Cash Ratio, Return on Investment (ROI), Return on Equity (ROE), and Net Profit Margin (NPM), of Financial Distress in Manufacturing Companies within the Consumer Goods Industry Sector that are listed on the Indonesian Stock Exchange. This study employs quantitative data. The findings and analysis presented in this study are as follows: The multiple linear regression test results indicate that the t-count value is 10.625, more significant than the t-table value of 2.03951. Additionally, the significance level of the t-count is 0.001, which is less than the significance level of 0.05. Therefore, we may infer that the t-count value is statistically significant. The ROI multiple linear regression test results indicate that the t-count value of 2.886 is statistically significant with a p-value of 0.007, compared to a t-table value of 2.03951 and a significance level of 0.05. Therefore, we can infer that the t-count value of 2.886 is significant. The t-value is 2.03951, and the significance level is 0.007, less than 0.05. The multiple linear regression analysis shows that the t-count for ROE is -2.897, which has a significance level of 0.007. Comparing this with the t-table value of 1.69552 at a significance level of 0.05, we may infer that the t-count value of 2.897 is greater than the t-table value of 1.69552, and the significance level of 0.007 is less than 0.05. The multiple linear regression analysis shows that the t-count value for NPM is -1.095, with a significance level of 0.282. Comparing this to the t-table value of 1.69552 at a significance level of 0.05, we may conclude that the t-count value of 1.095 is less than the t-table value and is not statistically significant. The F-table test yielded a result of 2.67 with an error rate of 5%. The acquired F-count was 50.596, more significant than the F-table value of 2.67, indicating a significant difference with a significance level of 0.002, less than the threshold of 0.05.